1970
DOI: 10.1029/jb075i032p06539
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectra of particulate silicates under simulated lunar conditions

Abstract: Infrared spectra have been acquired under simulated lunar conditions that demonstrate that, contrary to popular belief, features of high spectral contrast are available for small‐particle‐size samples. The spectral information occurs in the form of emission maxima that are associated with the principal Christiansen frequencies, and these maxima are diagnostic of gross composition. The features represent a 5 to 30% effect, depending on particle size and composition. The effect is explained in terms of the sharp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 7 publications
6
40
0
Order By: Relevance
“…1). The spectral behavior of thick dust mantles have been extensively studied (e.g., Korb et al, 1999;Salisbury and Wald, 1992;Logan and Hunt, 1970;Conel, 1969). These studies have concluded that there is generally a decrease in the spectral contrast of primary absorption features in the measured emissivity of particulate samples compared to their solid form.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…1). The spectral behavior of thick dust mantles have been extensively studied (e.g., Korb et al, 1999;Salisbury and Wald, 1992;Logan and Hunt, 1970;Conel, 1969). These studies have concluded that there is generally a decrease in the spectral contrast of primary absorption features in the measured emissivity of particulate samples compared to their solid form.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…There are numerous difficulties associated with using MIR spectroscopy to analyze remote sensing data from an airless body like the Moon, because most MIR emissivity data to which we compare our remote sensing data have been collected under terrestrial conditions. Early work (e.g., Conel, ; Henderson & Jakosky, ; Logan & Hunt, ; Nash et al, ; Salisbury et al, ) has shown the importance of environmental conditions (e.g., pressure, temperature of the surrounding medium, and illumination conditions) when measuring MIR spectra and how features can shift in both position and spectral contrast due to variations in those conditions. Recent studies (Donaldson Hanna, Thomas, et al, ; Donaldson Hanna, Wyatt, et al, ; Donaldson Hanna et al, , ; Lucey et al, ) have sought to produce MIR spectra that more closely match those measured by Diviner to optimize our ability to interpret lunar spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of H-O-H bending vibration at 6.1 micron in the spectra under vacuum precludes the presence of surface adsorbed water in the sample. Most of the vibrational bands observable between 8 and 16 µm appear strongly reduced in the vacuum emissivity spectrum with respect to the purged emissivity, due to thermal gradients in the sample (Logan and Hunt 1970) and to the weakening (disappearance in high vacuum) of the transparency feature in vacuum (Salisbury et al 1991). On the other hand some overtones below 7 µm are more prominent with respect to the other spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 77%